Pengaruh Minuman Serbuk Hytensol (Hypertension Solution) Terhadap Tekanan Darah Tikus (Rattus Norvegicus Galur Wistar) Hipertensi - Mira Ardiningsih; Aladhiana Cahyaningrum; Reni Sofiyatin; Fifi Luthfiyah (Jurnal Gizi Prima (Prime Nutrition Journal), 2018)
Background. The prevalence of NTB hypertension patients is 16.67% higher than the national prevalence that is 9.5% in 2013. Hytensol Drink Powder (MSH) contains 1388 mg of potassium and 15 mg sodium per 100 g.Research Methods. This research was conducted in the laboratory of Food Technology Science Department of Nutrition Poltekkes Kemenkes Mataram, Pharmacology Laboratory and Physiology Laboratory Faculty of Medicine Brawijaya University, Malang in May-June 2018 with pretest posttest with control group design, using 10 males white rat tail divided into 5 each groups into the control group and the treatment group. The subjects were given 5% w/v NaCl for 7 days to make hypertension. The treatment group was given MSH 0,36 g/100 g mouse BB for 7 days and blood pressure measurement before and after intervension. Statistical analysis used are shaipro wilk for normality test, independent T-test and paired sample T-test.Research Result. The mean blood pressure of the study subjects before the intervention for the control group and the treatment group was 143.75/110.25 mmHg and 143.5/116.25 mmHg to 156.25/109 mmHg and 104.75/77.75 mmHg (p=0.05). The mean decrease in systolic blood pressure in the treatment group reached 38.75 mmHg while a decrease of ≥20 mmHg can be said to have antihypertensive effect.Conclusion. Hytensol drink powder could decrease the rats (Rattus norvegicus strain Wistar) hypertensions blood pressure and has an antihypertensive activity.